Psychosocial and Work-Related Factors Associated with Musculoskeletal Pain among Office Workers in Gorgan, North of Iran - Mohammad Aryaie; Zahra Youefi; Samane Karimi; Danial Bagheri; Fozieh Bakhsha; Seyed Yaghob Jafari; Alireza Heidari; Kamal Mirkarimi; solmaz halako (Golestan University Of Medical Sciences, 2017)
Introduction:Mental health refers to emotional and psychological well-being, impairment of which may adversely affect an individual's cognitive or social functioning, making it harder to cope with the demands of daily life. According to the biopsychosocial paradigm and, common psychological symptoms, such as low mood, importantly influence the occurrence and prognosis of musculoskeletal pain. The aim of this study is to survey of association musculoskeletal pain with Psychosocial and work-related factors among office staff in Gorgan. Methods and Material: This descriptive and analytical study was performed among office workers in Gorgan in 2016. By cluster sampling method 675 office staff was included to be interviewed from the 18 occupational sectors. Data were collected on individual factors, negative affectivity, workplace factor, work station and task demand, psychosocial risk factors, work environment and experience of pain during the past 12 months. With Nordic Musculoskeletal Questionnaire (NMQ-E, Self-Administered Physical Activity Survey and the standardized Dutch Musculoskeletal Questionnaire. Data were analyzed by logistic regression in spss version 16.Results:Among all participants, 17.3 % reported neck pain, and it was 8.4 % and 20% for shoulder and low back pain, respectively. Moreover, 6.4% of these patients had pain in more than one body area. Factors including adjusted back rest on chair, work with bent head, hours worked per week and also supervisor support and sex were significant for the neck pain (p < 0.001). Factors consist of staring at the screen, forearm parallel to the floor while working, Sitting at work station before taking a break, sitting in awkward postures during the work, sex, age group and negative affectivity remained significant for low back pain. Conclusion: Excessive use of the computer system combined with a poorly designed workstation, repetitive computer work, lack of rest time at work, the role of individual factors such as age, sex, and lack of awareness of the dangers of environmental and psychosocial factors in workplace formed risk factors that are associated with musculoskeletal disorders, then, it is basically necessary to identify mentioned factors to solve and improve disorders.